English English - Salsa Fajrina Ghaisani; Yusron Saadi; Ery Setiawan; Yasa I Wayan; Salehudin Salehudin; Agus Suroso (Jurnal Penelitian Pendidikan IPA, 2024)
River diversion is a procedure carried out prior to constructing a dam. It is conducted by diverting water from the main river so that the main dam construction work can be executed at a specifically dry area. In Meninting Dam, the diversion system consists of two main structures, namely cofferdam and diversion tunnel that is equipped with a navigation structure at the upstream part of the tunnel. During the construction, cofferdam experienced overtopping on June 17, 2022. The overtopping most likely occurred because of the diversion tunnel’s inability to divert the actual flood effectively during the construction. Therefore, this research aimed to analyse the effectiveness of Meninting Dam’s proposed diversion tunnel against design flood discharge for a return period of 25 years. The data used in this research were the updated version of the ones used to design the whole construction of Meninting Dam’s diversion system, while the flow conditions along the diversion tunnel were analysed using HEC-RAS. At the same time, the analysis was also carried out using the Level Pool Routing Method as a comparison. The analysis results show that the design flood discharge for a return period of 25 years in Meninting Dam Watershed is 265,62 m3/s. This causes the water level along the diversion tunnel reach el. +165,95 m above sea level. Taking into account that the cofferdam crest elevation is at +170,00 m above sea level, it could be concluded that Meninting Dam’s proposed diversion tunnel, which is 4 m wide and 4 m tall is able to divert the design flood discharge for a return period of 25 years effectively. The investigation results in Meninting Dam Watershed show that the main cause of the overtopping was heavy precipitation. This caused the increasing water level at the upstream part of the cofferdam that resulted to its inability to function properly, taking into account that it was still under construction when it occurred